You talkin' to me? : rhetoric from Aristotle to Obama - Leith, Sam (London, England : Profile Books, 2011)
Rhetoric is what gives words power. It's nothing to be afraid of. It isn't the exclusive preserve of politicians: it's everywhere, from your argument with the insurance company to your plea to the waitress for a table near the window. This book examines how people have taught, practiced and thought about rhetoric from its Attic origins onwards.
CONTENTS: Introduction -- Rhetoric Then and Now -- The first part of rhetoric: Invention --The three branches of Oratory -- Thus It Can Be Shown -- Appendix: Glossary and Key Concepts
Paperback edition published in 2012
Includes bibliographical references and index
Keywords: Rhetoric; Rhetoric -- History